Immunotherapeutic progress and application of bispecific antibody in cancer - Kang, Jingyue; Sun, Tonglin; Zhang, Yan (Frontiers in Immunology, 2022)
Bispecific antibodies (bsAbs) are artificial antibodies with two distinct antigen-binding sites that can bind to different antigens or different epitopes on the same antigen. Based on a variety of technology platforms currently developed, bsAbs can exhibit different formats and mechanisms of action. The upgrading of antibody technology has promoted the development of bsAbs, which has been effectively used in the treatment of tumors. So far, 7 bsAbs have been approved for marketing in the world, and more than 200 bsAbs are in clinical and preclinical research stages. Here, we summarize the development process of bsAbs, application in tumor treatment and look forward to the challenges in future development.